Podocyte Endocytosis in Regulating the Glomerular Filtration Barrier - Tian, Xuefei; Bunda, Patricia; Ishibe, Shuta (Frontiers in Medicine, 2022)
Endocytosis is a mechanism that internalizes and recycles plasma membrane components and transmembrane receptors via vesicle formation, which is mediated by clathrin-dependent and clathrin-independent signaling pathways. Podocytes are specialized, terminally differentiated epithelial cells in the kidney, located on the outermost layer of the glomerulus. These cells play an important role in maintaining the integrity of the glomerular filtration barrier in conjunction with adjacent basement membrane and endothelial cell layers within the glomerulus. An intact podocyte endocytic machinery is critical in their homeostatic maintenance. By studying pathologic human genetic mutations and through generation of genetically engineered mouse models, numerous studies suggest that impaired podocyte endocytosis largely contributes to the pathophysiology of proteinuria in chronic kidney disease. Here, we review the mechanism of cellular endocytosis and its regulation in podocyte injury in the context of glomerular diseases. A thorough understanding of podocyte endocytosis may shed novel insights into its biological function to maintain a functioning filter and offer potential targeted therapeutic strategies for proteinuric glomerular diseases.